Touristic and Chauvinistic Perspectives on the Arctic in the Italian Popular Press Some cases of literary and artistic reception, from the fin-de-siècle to the Fascist era - d’Ayala Valva, Margherita (Nordlit, 2008)
In this paper, I will focus on non-scientific Italian perspectives on the Arctic at the beginning of the 20th century. Based on selected journalistic travel writings and on children's books and their pictorial and photographic illustrations, I will examine some illustrative instances of the Italian perception of the Great North during this era. More specifically, I will focus on the Duke of Abruzzi's Polar Expedition of 1900 and Umberto Nobile's expedition of 1928. These cases are of particular interest in terms of artistic and literary reception, popular imagery, and political implications.